Preparation, characterization, and antibacterial activity of diclofenac-loaded chitosan nanoparticles - Fulwah Yahya Alqahtani; Fadilah Sfouq Aleanizy; Eram El Tahir; Bushra T. Alquadeib; Ibrahim A. Alsarra; Jouri S. Alanazi; Hosam Gharib Abdelhady (Elsevier, 2019)
Emerging antibiotic resistance necessitates the development of new therapeutic approaches. Many studies have reported the antimicrobial activity of diclofenac sodium (DIC) and chitosan nanoparticles (CNPs). Hence, this study aimed to prepare non-antibiotic DIC-loaded CNPs (DIC.CNPs) and characterize their in vitro antibacterial activity. DIC.CNPs were prepared from low and high molecular weight (LMW and HMW, respectively) chitosan using an ionic gelation method. Prepared NPs were characterized, and their antibacterial activity against gram-positive Staphylococcus aureus and Bacillus subtilis was evaluated using the agar diffusion and broth dilution methods. The particle size, polydispersity index (PDI), and encapsulation efficiency of the formulated DIC.CNPs increased with increasing MW of chitosan. The prepared NPs showed a narrow size distribution with low PDI values (0.18 and 0.24) and encapsulation efficiency (29.3% and 31.1%) for LMW.DIC.CNPs and HMW.DIC.CNPs, respectively. The in vitro release profile of DIC from the DIC.CNPs was biphasic with a burst release followed by slow release and was influenced by the MW of chitosan. DIC.CNPs exhibited significantly higher antibacterial activity against S. aureus (minimum inhibitory concentration [MIC90] LMW.DIC.CNPs = 35 µg/mL and MIC90 HMW.DIC.CNPs = 18 µg/mL) and B. subtilis (MIC90 LMW.DIC.CNPs = 17.5 µg/mL and MIC90 HMW.DIC.CNPs = 9 µg/mL) than DIC alone did (MIC90 DIC = 250 and 50 µg/mL against S. aureus and B. subtilis, respectively). The antibacterial activity was influenced by pH and the MW of chitosan. Collectively, these results may suggest the potential usefulness of DIC.CNPs as non-antibiotic antibacterial agent necessitating further future studies to asses the stability of DIC.CNPs prepared. Keywords: Chitosan nanoparticles, Non-antibiotic, Antimicrobial, Low-molecular weight chitosan, High-molecular weight chitosan